Perbandingan Kadar Estrogen Serum dan TGF β-1 Plasma pada Penderita BPH-Non BPH di Atas 50 Tahun dan Usia Muda - Eriawan Agung Nugroho; Selamat Budijitno (MEDIA MEDIKA INDONESIANA, 2013)
ABSTRACT Comparison of estrogen serum and TGF β-1 plasma levels in benign prostate hyperplasia (BPH) and non BPH patients, among 50-years old and young patients.Background: Benign prostatic hyperplasia (BPH) is often found in older men. This disease affects an estimated 70% of men over 60 years, increased by 90% in men over 80 years age. Many scientists tried explores the hypothesis of the mechanism of occurrence of BPH. The purpose of study compared the levels of estrogen and transforming growth factor (TGF) ß-1 in plasma related to the development of BPH, in BPH patients and non-BPH over 50 years and young age.Methods: A clinical analysis study was carried out on subjects who were divided into 3 groups: patients with BPH >50 years, non-BPH >50 years and younger non-BPH aged 30-40 years. T-test was used to analyze the data. Serum estrogen and plasma TGF β-1 were assessed using ELISA method.Results: There was no significant difference (p=0.129) between the level of estrogen in BPH patients >50 years (140.091±43.649) and non BPH patients >50 years (63.69±18.757) but there was a significant difference (p=0.015) between level of plasma TGF ß-1 BPH patients >50 years (10.47±4.507) and non BPH patients >50 years of age (25.8±16.1103). No significant differences (p=0.348) were found between serum estrogen level of non-BPH >50 years (63.69±18.757) and the young age (57.17±10.2748), and between plasma TGF ß-1 non-BPH group >50 years (25.80±16.1103) and the younger age group (31.4±17,576)(p=0.496).Conclusion: There is difference in the level of TGF ß-1 between younger and older age groups. Elderly men are recommended for early prostate examination, because at the age of 50 years there is already a tendency of enlarged prostate gland. Levels of transforming growth factor β-1 can predict prostate enlargement.Keywords: Estrogen, TGF ß-1, benign prostate hyperplasia (BPH)ABSTRAKLatar belakang: Benign prostate hyperplasia (BPH) sering ditemukan pada pria usia lanjut. Penyakit ini terjadi pada 70% pria di atas 60 tahun, dan meningkat hingga 90% pada pria di atas 80 tahun. Banyak ilmuwan mencoba mengetengahkan hipotesis faktor yang berpengaruh terjadinya BPH. Tujuan penelitian ini membandingkan tingkat estrogen dan transforming growth factor (TGF) ß-1 dalam plasma terkait pembentukan BPH.Metode: Penelitian klinik analitik dilakukan pada subyek yang dibagi 3 kelompok, pasien dengan BPH >50 tahun, pasien non-BPH berusia >50 tahun dan muda non-BPH berusia 30-40 tahun. Analisis data dengan uji beda kadar estrogen serum dan TGF β-1 plasma ketiga kelompok. Kadar TGF ß-1 dan estrogen diukur dengan metoda ELISA.Hasil: Serum estrogen pasien BPH usia >50 tahun (140,091±43,649) lebih tinggi tetapi tidak berbeda bermakna (p=0,129) dibandingkan non BPH usia >50 tahun (63,69±18,757). Estrogen serum non-BPH usia >50 tahun (63,69±18,757) dibandingkan usia muda (57,17±10,2748) tidak berbeda bermakna (p=0,348). TGF ß-1 plasma pasien BPH usia >50 tahun (10,47±4,507) lebih rendah (p=0,015) dibandingkan pasien non BPH usia >50 tahun (25,8±16,1103). TGF ß-1 plasma kelompok non-BPH >50 tahun (25,80±16,1103) dibandingkan kelompok usia muda (31.04±17,576) tidak berbeda bermakna (p=0,496).Simpulan: Ada perbedaan antara tingkat TGF β-1 pada kelompok yang lebih tua. Laki-laki usia tua disarankan lebih dini melakukan pemeriksaan prostat, usia >50 tahun cenderung didapatkan pembesaran kelenjar prostat. Pemeriksaan kadar TGF -1 dapat memprediksi risiko pembesaran kelenjar prostat.